2020
DOI: 10.1111/petr.13849
|View full text |Cite
|
Sign up to set email alerts
|

Empowering patients to adhere to their treatment regimens: A multifaceted approach

Abstract: It is well‐recognized that adolescence and early adulthood are a high‐risk period for non‐adherence with treatment regimens in solid organ transplant recipients, leading to high rates of rejection and graft loss (Transplantation, 92, 2011, 1237; Pediatr Transplant, 9, 2005, 381; Transplantation, 77, 2004, 769). Preventing medication non‐adherence is the holy grail of transplant adolescent care. If we can determine how best to support our patients in taking their daily medications as prescribed, we can improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…This study indicates that type 2 DM respondents who received treatment and adhered to it could reduce FBG levels and PPBG levels more successfully than non-adherent respondents. 12,25,26 In this study, the treated group showed decreased FBG and PPBG within 4 years. After respondents obtained check-up laboratory results from the Health Research and Development Agency (every 2 years), the respondents were given a referral to a doctor for further DM diagnosis examination.…”
supporting
confidence: 48%
“…This study indicates that type 2 DM respondents who received treatment and adhered to it could reduce FBG levels and PPBG levels more successfully than non-adherent respondents. 12,25,26 In this study, the treated group showed decreased FBG and PPBG within 4 years. After respondents obtained check-up laboratory results from the Health Research and Development Agency (every 2 years), the respondents were given a referral to a doctor for further DM diagnosis examination.…”
supporting
confidence: 48%
“…One of the major challenges faced by youth, adolescents, and young adults after transplant is medication adherence. While multiple studies have investigated the factors that lead to nonadherence 7,24,[43][44][45] and ways to improve adherence after transplant, 46 nonadherence continues to be a problem. 23,44 While structured tools -such as barrier assessments -provide opportunities to help address common issues faced by individuals after transplant, 47 individuals face challenges that are personal and unique.…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits are of significant importance for adherence behavior ( Axelsson et al, 2011 ; Hazrati-Meimaneh et al, 2020 ); people defined as “a worrying kind of person” (i.e., neuroticism; Costa and McCrae, 1992 ) tend to adhere low and in an inappropriate way to management suggestions ( Bruce et al, 2010 ; Axelsson et al, 2011 ). On the contrary, conscientious people, because of their tendency to trust their abilities to manage their lives, tend to adhere to the prescribed treatment and abide to doctors’ advice ( Rosengren et al, 2004 ; Pruette and Amaral, 2021 ), while extraverted and agreeable individuals are favored in developing positive relationships with health providers and caregivers, so to make use of social support facilitating health management ( Berkman et al, 2000 ; Hazrati-Meimaneh et al, 2020 ).…”
Section: Personality and Cardiotoxicity Of Anticancer Treatments: Is There A Relationship?mentioning
confidence: 99%